Effect of Destination Image on Destination Selection, Event Organizer Satisfaction - Khongrat, Etty (KnE Social Sciences, 2024)
In business of organizing MICE events, the place (venue) is the main factor in determining destinations that are in accordance with the concept of the event. The destination image is important for an event organizer to determine the host destination for a MICE event. This study aims to explain the influence of destination image on destination selection and satisfaction from event organizers. Data collection was carried out using a questionnaire with a random sampling technique on 70 respondents who were in the MICE destination of Jakarta. The data analysis used in this research is general structured component analysis (GSCA). The results of this research prove that destination image has a significant effect on destination selection with a path coefficient value of 0.299 with a P-value of <0.001. It has a positive relationship, then destination selection has a significant effect on satisfaction with a path coefficient of 0.1013 and p-value of 0.047, while destination image has a significant effect on the satisfaction of 0.101 with a value < 0.001. Keywords: destination image, destination selection, satisfaction